Pattern and Outcome of Organophosphorus Poisoning Cases in Bheri Hospital, Nepal - Mandal, Rajesh Kumar; Shakya, Nirmal; Risal, Sanket Kumar (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Organophosphorus (OP) are frequently used as pesticides and the most common agents of poisoning in developing countries including Nepal. There is paucity of data about characteristics of organophosphorus poisoning in our localities. Therefore, we aimed to evaluate its clinical pattern and factors affecting outcome. METHODS: It was a cross-sectional study conducted in Bheri Hospital Nepalgunj between 15th July 2019 to 14th July 2020. The hospital records of patients of acute organophosphorus poisonings were collected. Data regarding age, gender, predisposing factors, duration of hospitalization and outcome of the patients were recorded. Data was analyzed using SPSS 20. RESULTS: A total of 53 patients out of which 22(41.5%) were male and 31(58.49%) were female with F:M ratio of 1.40: 1. The maximum number of the patients 25(47.16%) were in the age group of 20 to 40 years. Incidence of poisoning was more common in married patients 36(67.92%) The suicidal motive for poisoning was found in 49 cases (92.45%). The most commonly used organophosphorus poison was Dichlorvos 32(60.34%) followed by methyl parathion 14(26.41%). Domestic quarrel was the most common predisposing factor 32(60.37%). 45(84.90%) of the patients were discharged after successful treatment while there was mortality of 3 patients (5.66%). CONCLUSIONS: Organophosphorus poisoning is a common mode of suicidal attempts leading to morbidity and mortality every year. Strict policies against the free availability and sale of insecticides is required to control organophosphorus poisoning. Mental health education programme should be conducted for the prevention of suicide and poisoning.